FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN DIET PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS KECAMATAN PASAR MINGGU TAHUN 2018 - Youvita Indamaika Simbolon; Triyanti Triyanti; Ratu Ayu Dewi Sartika (Jurnal Kesehatan Komunitas, 2019)
Background: The level of dietary adherence in Indonesia is still low. Diet in maintaining food is often become an obstacles because the patient is still tempted by all food that can worsen their health. Met The purpose of this study is to determine the factors that associated with dietary adherence in type 2 diabetes mellitus patients. This study was using a cross-sectional design. The samples studied were all type 2 diabetes mellitus type 2 with the age range 25-65 years was outpatient, samples were taken with non-random sampling method with purposive sampling of 130 people. Data were collected through anthropometric measurements, filling-out questionnaires, 1x24 hour food recall and dan (semi-quantitative food frequency questionnaire) SFFQ form. Results: The results showed 13.8% of respondents were diet-compliant. There were significant relationship between gender (p=0.008) and length of suffering (p=0.044) with between dietary adherence. The result of logistic regression test showed that the duration of suffering is the dominant factor associated with dietary adherence in type 2 diabetes mellitus patients. Conclusion: Type 2 diabetes mellitus patients were expected to pay attention to the diet recommended and carry it out well, to actively to improve the knowledge related to the disease diabetes mellitus and related to the other factors and still preserve diet that has been run for who has long been suffering from type 2 diabetes mellitus.